Türk anayasa tarihinde asli kurucu iktidarların meşruluğu sorunu - Şahin, Engin (My University, 2013)
Anayasa, Meşruiyet, Asli Kurucu İktidar ÖZET TÜRK ANAYASA TARİHİNDE ASLİ KURUCU İKTİDARLARIN MEŞRULUĞU SORUNU Türkiye’de anayasa problemi Cumhuriyetin ilanından günümüze varolagelmiştir. Doksan yıllık Cumhuriyet tarihinde dört farklı anayasaya sahip olan Türkiye’de, çok defa anayasa değişikliği yapılmasına rağmen, bunların hiçbiri beklenen sonucu vermemiş ve anayasa tartışmaları sonlanmamıştır. Anayasa üzerine yapılan tartışmaların kilit noktasını, anayasayı hazırlayan asli kurucu iktidar yetkisinin kimler tarafından kullanıldığı oluşturmaktadır. Bu doktora tez çalışmasında, ulus-devlet olarak, yaklaşık bir asırlık geçmişi bulunan Türkiye Cumhuriyeti tarihindeki dört anayasanın (1921, 1924, 1961, 1982) hazırlanış biçimleri üzerinden asli kurucu iktidarların meşruiyeti incelenmiştir. Bu amaçla, öncelikle anayasa, asli kurucu iktidar ve meşruiyet kavramlarının tanımları yapılmıştır. Daha sonra, anayasa ve asli kurucu iktidarın meşruiyetini kazanabileceği şartlar ortaya konulmuştur. Son olarak, bu şartlar çerçevesinde, Türkiye’deki asli kurucu iktidarların ortaya çıktığı dönemler, oluşumları ve anayasaları nasıl hazırladıkları anlatılarak, meşruiyetlerini sorunlu kılan sebepler sıralanmıştır.

THE LEGITIMACY PROBLEM OF THE PRIMARY CONSTITUENT POWER IN TURKISH CONSTITUTIONAL HISTORY The problem of constitution in Turkey has existed since the proclamation of the Republic. Although the Turkish Republic during her past 90 years have had four different constitutions and also many amendments in these constitutions, none of those attempts has offered an eventual solution and finished the arguments over the problem of constitution. The key point of the arguments over the problem has been the question by whom the authority for the primary constituent power has been used. In this dissertation, the legitimacy of the primary constituent power is analyzed on the basis of the preparation processes of those four constitutions (1921, 1924, 1961, 1982) in the history of the Turkish Republic, a nation state which is almost a century year old. To that end, firstly the concepts of constitution, the primary constituent power and legitimacy are defined. Next, the conditions which could legitimate the emergence of constitutions and primary constituent powers are to follow. Pursuant to these conditions, lastly, the factors troubling the legitimacy of the primary constituent powers in Turkey are enumerated by unfolding the contexts in which these powers emerged and prepared the regarding constitutions. Constitution, Legitimacy, Constituent
Keywords: Anayasa Tarihi; Anayasalar; Kamu yönetimi; Türkiye; Türkiye --Ssiyaset ve Yönetim